85 Cultured thymus tissue is a rich source of immune cells for MHC restriction studies. (22nd November 2019) - Kelly, Paul; Obiri-Yeboa, Irene; Marriott, Clare; Howley, Evey; Kreins, Alexandra; Gilmour, Kimberly C; Buckland, Matthew; Davies, Graham
Abstract : Thymus transplant represents the gold standard treatment for complete T-cell deficiency caused by athymia in patients with DiGeorge syndrome. Currently, donor thymus tissue is not MHC matched to the recipient and it is unclear whether closer HLA relatedness would improve T-cell reconstitution. In preparation for transplant, thymus tissue is harvested from donors undergoing cardiac surgery, sliced into 1 mm thick sections and cultured for up to 21 days. During this culture period the thymus sections are irrigated regularly with culture media. We hypothesise that this culture media provides a rich source of donor immune cells for subsequent MHC restriction studies, allowing us to investigate the interactions between donor APCs and recipient T-cells. During routine thymus culture in preparation for transplant, thymus culture media was harvested and immune cells were pelleted by centrifugation. Immune cell populations were subsequently analysed by flow cytometry, with staining for CD4+ and CD8+ T-cells, CD19+ B-cells, CD16/56+ NK-cells and CD14+ monocytes. In addition to immunoprofiling, immune cells were cryopreserved for future investigations. During the first five days of culture T-cells represented the largest population in the culture media (CD4+ cells 36.3% of CD45 cells; CD8+ cells were 35.4% of CD45 cells). CD14+ cells were 9.3% of total CD45 cells, B cells were 8.1% of total CD45 cells while relative populations of NK-cells and NKT-cells were low (0.2% and 0.8% of total CD45 cells respectively). Our results indicate that the thymus culture media represents a rich source of donor immune cells, both antigen presenting and T-cells, which can be cryopreserved for MHC restriction studies. Future work will establish an assay for the differentiation of these donor derived CD14+ antigen presenting cells into dendritic cells in order to investigate the effects of MHC restriction and measure T-cell antigen specific responses between donor antigen presenting cells and recipient T-cells.